2011
DOI: 10.1371/journal.pone.0028629
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 Promotes CD95-Induced Apoptosis in B Cells via the IFN-γ/STAT1 Pathway

Abstract: Interleukin-7 (IL-7) concentrations are increased in the blood of CD4+ T cell depleted individuals, including HIV-1 infected patients. High IL-7 levels might stimulate T cell activation and, as we have shown earlier, IL-7 can prime resting T cell to CD95 induced apoptosis as well. HIV-1 infection leads to B cell abnormalities including increased apoptosis via the CD95 (Fas) death receptor pathway and loss of memory B cells. Peripheral B cells are not sensitive for IL-7, due to the lack of IL-7Ra expression on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…Our results are consistent with the elevated levels of BAFF (also known as BLyS) observed during HIV-1 infection, in association with hypergammaglobulinemia [58]. We also found that Fas expression on B cells is modulated by the release of interferon-g (IFN-g) from IL-7-treated T cells [55]. The increased Fas expression further sensitizes the B cells to undergo Fas-mediated apoptosis.…”
Section: Influence Of Cytokines On B-cell Homeostasissupporting
confidence: 88%
See 1 more Smart Citation
“…Our results are consistent with the elevated levels of BAFF (also known as BLyS) observed during HIV-1 infection, in association with hypergammaglobulinemia [58]. We also found that Fas expression on B cells is modulated by the release of interferon-g (IFN-g) from IL-7-treated T cells [55]. The increased Fas expression further sensitizes the B cells to undergo Fas-mediated apoptosis.…”
Section: Influence Of Cytokines On B-cell Homeostasissupporting
confidence: 88%
“…We showed recently that cytokines commonly associated with lymphopenia and increased T-cell activation might strongly influence B-cell homeostasis [55,11]. These studies suggested that IL-7, present in elevated concentrations in the circulation of several T-cell-depleted individuals [33], may interfere with B-cell proliferation and survival in novel and nonantigen-specific manners.…”
Section: Influence Of Cytokines On B-cell Homeostasismentioning
confidence: 99%
“…These early IFNγ-dependent signals are required for subsequent proliferation and differentiation following stimulation with IL-21 and TLR7/8 ligand. IFNγ is not, in and of itself, a B cell mitogen and has, in fact, been reported to induce apoptosis of human B cells (64, 65). However, we find that IFNγ synergizes with TLR7/8 ligand signals to promote multiple rounds of B cell proliferation – an important prerequisite of ASC differentiation (66).…”
Section: Discussionmentioning
confidence: 99%
“…Although such unresponsiveness is frequently achieved by loss of cytokine receptor expression , other mechanisms, including the abnormal activity of a negative regulator of cytokine signalling, may also play a role. SOCS1, in particular, might contribute to induce loss of responsiveness of tumour cells to HIV‐induced cytokines, for example, loss of responsiveness to INF‐γ, which causes B‐cell defects and apoptosis .…”
Section: Discussionmentioning
confidence: 99%